Gender and Organizational Performance: Determinants of Small Business Survival and Success - Kalleberg, Arne L.; Leicht, Kevin T. (Academy of Management Journal, 1991)
This research explores the effect of gender on organizational performance. Data used in the analysis was collected from small businesses in South Central Indiana from 1985-1987. The businesses were from the food and drink, computer sales and software, and health industries. Of the businesses surveyed, 312 were headed by men while 99 where headed by women. On average, these individuals were 44-45 years of age. Organizational performance is examined through two different concepts, survival and success. The results indicate that women were not more likely to go out of business than men, and only prior self-employment had different effects for men and women. Further, there was not a difference in this area among the differing industries. The results also indicate that both genders were equally confident and believed they had the ability to influence business outcomes. As for the success of these businesses, there again was no difference between the males and females with respect to earnings growth. These results are contrary to the traditional thinking that men have an advantage over women with respect to entrepreneurship and organizational performance. Since the dataset used in this analysis was limited in scope, further research is necessary to determine if these results will hold true across other industries. (SRD)